Detection of procalcitonin (PCT) using the double antibody sandwich method based on fluorescence resonance energy transfer between upconversion nanoparticles and quantum dots. Issue 9 (12th February 2018) - Zhou, Yang; Shao, Xiangming; Han, Yuwang; Zhang, Hongman
Abstract : This is the first attempt to detect PCT using the antibody–antigen–antibody "sandwich" immunoassay based on FRET. Abstract : A nanosensor is designed using a double antibody sandwich method based on fluorescence resonance energy transfer (FRET) between NaYF4 (Yb, Er) upconversion nanoparticles (UCNPs) and CdTe quantum dots (QDs) for the determination of procalcitonin (PCT). The UCNPs (donor) and CdTe QDs (acceptor) were modified separately with two PCT monoclonal antibodies, and they were bound together through a specific immune reaction via the addition of PCT antigen. The fluorescence intensity of UCNPs was quenched because of the resonant energy transferred between upconversion nanoparticles and quantum dots. Under the optimal conditions, the fluorescence quenching efficiency showed a linear response to the PCT concentration with values ranging from 0.1 to 10 ng mL −1 and a detection limit of 0.25 ng mL −1 . This method can be easily extended to the double antibody sandwich assay with potential applications in in vitro diagnostics (IVD).